CEOs' regulatory focus and firm internationalization: The moderating effects of CEO overconfidence, narcissism and career horizon. Issue 3 (June 2023) - Biru, Ashenafi; Filatotchev, Igor; Bruton, Garry; Gilbert, David
Abstract: While the international business literature has mainly focused on the firm- or industry-level antecedents of internationalization strategies, scholars have recently advocated a greater focus on the microfoundations of firms' strategic decisions. Building on the regulatory focus theory, this study focuses on how CEO promotion and prevention foci impact firm internationalization. Looking into dispositional and situational attributions, this study also theorizes how these factors moderate the relationship between a CEO's psychological motivations and firm internationalization. Using data from publicly traded US firms listed in the Fortune 500, the findings of this study show that a CEO's promotion focus is positively associated with the extent of a firm's internationalization, whereas a CEO's strong prevention focus limits the extent of a firm's internationalization. The findings also reveal that the relationship between a CEO's regulatory focus and the extent of a firm's internationalization is moderated by a CEO's overconfidence, narcissism, and career horizon. These findings have important research and managerial implications for firms engaged in international business. Highlights: CEOs' regulatory focus have not been well explored in the context of international business. The study analyzes potential relationships between regulatory focus of CEOs and their internationalization decisions. CEOs' regulatory focus have considerable impact on firm internationalization. We highlight that a CEO's regulatory focus is at least partly dependent on other dispositional and situational conditions. We outline a future research agenda that can help advance on CEOs' psychological motivations and international business.